Optical variability of Active Galactic Nuclei from Catalina Surveys data. (May 2020) - Laurenti, M; Vagnetti, F; Middei, R
Abstract: The Catalina Real-Time Transients Survey (CRTS) has observed a large fraction of the sky (∼33000 deg 2 ), detecting more than 500 million objects several times, so providing a statistically consistent database of multi-epoch observations of various Galactic and extragalactic sources. Therefore, it is particularly suitable to perform variability studies over different timescales. The analysis of active galactic nuclei (AGN) flux variations provides an invaluable insight on these sources since variability encodes the underlying physics of the emitting regions. In this context, we present an optical variability analysis based on a statistical sample of AGN derived from the crossmatching of a preexistent multi-wavelength based catalogue (Multi-Epoch X-ray Serendipitous AGN Sample 2, or MEXSAS2) with the Catalina Surveys Data Release 2 (CSDR2). Visual inspection of the light curves and a novel estimate of the photometric error associated to the Catalina Sky Surveys have been mandatory to obtain a refined sample of 400 quasars widespread over a large interval of redshift (0.1 < z < 3.4) and bolometric luminosity (10 45 erg/s ≲ LBo i ≲ 10 48 erg/s). We exploit the structure function (SF) method, which works in the time domain, to investigate the short (few days) to long term (up to ∼ 10 years) variability properties of our sample. Our variability analysis suggests a possible underestimate of the photometric errors, which strongly affect the structure functions.